A Critical Role of δ-Opioid Receptor in Anti-microglial Activation Under Stress - Xu, Yuan; Zhi, Feng; Peng, Ya; Mao, Jiahao; Balboni, Gianfranco; Yang, Yilin; Xia, Ying (Frontiers in Aging Neuroscience, 2022)
Microglia are involved in the regulation of cerebral homeostasis and pathogen confrontation. There is, however, evidence showing that excessive microglia activation is implicated in various age-related cerebral diseases. On the other hand, microglia may experience complex changes of polarization in pathological insults, i.e., from a proinflammatory M1 to an anti-inflammatory M2 phenotype, which differentially contribute to the exacerbation or alleviation of cellular injury. Remolding the phenotype of microglia or inhibiting the excessive activation of microglia seems to be a promising approach against neurodegenerative pathologies. Since δ-opioid receptor (DOR) activation exhibits a strong protective capacity against various neuronal injuries, especially the hypoxic/ischemic injury, we asked if the DOR-induced neuroprotection is associated with its effect on microglia. We explored this fundamental issue by using pharmacological and genetic approaches in the BV2 cell line, a general type of microglial cells. The results showed that DOR expression significantly increased in the activated microglial M2 phenotype, but slightly decreased in the microglial M1 phenotype. Hypoxia induced dual polarizations of BV2 cells with an increase in DOR expression. Administration of a specific DOR agonist, UFP-512, largely inhibited lipopolysaccharide (LPS) or hypoxia-induced microglial M1 activation and inflammatory activity with high concentrations of UFP-512 being effective to reverse the interleukin-4 (IL4)-induced microglial activation. Consistent with these observations, inhibiting DOR or knocking-down DOR promoted the excessive activation of BV2 cells in both M1 and M2 directions, while DOR overexpression did the opposite. Furthermore, the PC12 cells exposed to the conditioned medium of BV2 cells treated by UFP-512 grew better than those treated directly with UFP-512 under LPS or hypoxic insults. DOR inhibitor naltrindole could block all the effects of DOR activation. The medium from the BV2 cells with DOR knock-down decreased the viability of PC12 cell, while the medium from the BV2 cells with DOR overexpression largely attenuated LPS or hypoxic injury in the PC12 cells. These first data suggest a close linkage between DOR expression/function and microglial polarization and a critical role of DOR in negative controlling microglial activation. Our work provides a novel clue for new protective strategies against neurodegenerative pathophysiology through DOR-mediated regulation of microglia.